(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The purpose of this research is to investigate the impact of Corporate Social Responsibility Disclosure (CSRD) on company value, with firm size as moderating variable. The research topic is mining businesses listed on the Indonesia Stock Exchange from 2018 to 2020. In this study, 10 firms were observed, yielding a total of 30 observations. In sampling, the non-probability sampling methodology with the purposive sampling method was employed, and data analysis techniques included multiple linear analysis and Moderated Regression Analysis (MRA). The study’s findings show that CSRD and company size have no significant impact on firm value; however, firm age has a significant positive impact on firm value. This study also demonstrates that company size cannot moderate (strengthen or weaken) CSRD, including social elements of firm value.